Financial Crisis, Creditor-Debtor Conflict, and Political Extremism - Gyozo Gyongyosi; Emil Verner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the effect of the 2008 financial crisis on the vote share of the populist far right. We use the foreign currency borrowing of households in Hungary as a natural experiment. During the crisis the unexpected and large depreciation of the domestic currency increased the debt burden of households borrowing in foreign currencies but not of households borrowing in the local currency. We use zip code level variation in the prevalence of foreign currency borrowing of households, and show that the exposure to the depreciation significantly affected political preferences. A 10 percent unanticipated rise in indebtedness increased the vote share of the far right by 2.2 percentage points. This effect explains one third of the increase of their popularity by the 2010 election. Foreign currency debtors' naveté, persistent extremist attitudes, local labor market shocks, and immigration do not account for this increase. We present evidence that the conflict between creditors and debtors about the resolution of the crisis is an important mechanism in the electoral success of the far right. The far right sided with debtors against creditors by advocating policies to help households with foreign currency loans.
Keywords: 330